Implementasi Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah Untuk Meningkatkan Mutu Pendidikan - Elynawati, Elynawati; Usman, Nurodin; Mawardi, Imam (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study aims to determine the implementation of the supervisory function of the DPRD Temanggung Regency in terms of planning, implementation, and evaluation, to find out the efforts made by the DPRD to improve the quality of education in Temanggung Regency and to find out the obstacles faced by the DPRD in overseeing the quality of education in Temanggung Regency. The research used is qualitative research, while the research approach used is descriptive qualitative research. The object of this research is the DPRD of Temanggung Regency. The method used in this study is a descriptive method that is carried out in a systematic, factual, and accurate manner regarding the facts, nature, and relationship of the phenomena being investigated. The data were obtained through interviews, document studies, and observation. The results of this study indicate that: (1) The implementation of the DPRD's supervisory function to improve the quality of education in Temanggung Regency from the planning, implementation, and evaluation side has been going well and in accordance with statutory regulations; (2) The efforts that have been made by the DPRD to improve the quality of education in Temanggung Regency are through the legislative function and through the budgeting function; (3) Obstacles faced by the DPRD in supervising the quality of education in Temanggung Regency are limited human resources, both in terms of numbers, educational background, the background of interest and level of understanding of DPRD Members regarding the supervisory function, limited time, limited authority, limited information and there is a wrong perception of the supervision carried out by the DPRD.